If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (a + bi)(6 + -7i) = 53 + 9i Multiply (a + bi) * (6 + -7i) (a(6 + -7i) + bi(6 + -7i)) = 53 + 9i ((6 * a + -7i * a) + bi(6 + -7i)) = 53 + 9i ((6a + -7ai) + bi(6 + -7i)) = 53 + 9i (6a + -7ai + (6 * bi + -7i * bi)) = 53 + 9i (6a + -7ai + (6bi + -7bi2)) = 53 + 9i (6a + -7ai + 6bi + -7bi2) = 53 + 9i Solving 6a + -7ai + 6bi + -7bi2 = 53 + 9i Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-6bi' to each side of the equation. 6a + -7ai + 6bi + -6bi + -7bi2 = 53 + -6bi + 9i Combine like terms: 6bi + -6bi = 0 6a + -7ai + 0 + -7bi2 = 53 + -6bi + 9i 6a + -7ai + -7bi2 = 53 + -6bi + 9i Add '7bi2' to each side of the equation. 6a + -7ai + -7bi2 + 7bi2 = 53 + -6bi + 7bi2 + 9i Combine like terms: -7bi2 + 7bi2 = 0 6a + -7ai + 0 = 53 + -6bi + 7bi2 + 9i 6a + -7ai = 53 + -6bi + 7bi2 + 9i Reorder the terms: -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 53 + -6bi + 7bi2 + 9i + -53 + 6bi + -7bi2 + -9i Reorder the terms: -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 53 + -53 + -6bi + 6bi + 7bi2 + -7bi2 + 9i + -9i Combine like terms: 53 + -53 = 0 -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 0 + -6bi + 6bi + 7bi2 + -7bi2 + 9i + -9i -53 + 6a + -7ai + 6bi + -7bi2 + -9i = -6bi + 6bi + 7bi2 + -7bi2 + 9i + -9i Combine like terms: -6bi + 6bi = 0 -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 0 + 7bi2 + -7bi2 + 9i + -9i -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 7bi2 + -7bi2 + 9i + -9i Combine like terms: 7bi2 + -7bi2 = 0 -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 0 + 9i + -9i -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 9i + -9i Combine like terms: 9i + -9i = 0 -53 + 6a + -7ai + 6bi + -7bi2 + -9i = 0 The solution to this equation could not be determined.
| 4x-8=2x-18 | | 5(x-3)=2x+2(x-5) | | 5/8(12+3x)=15 | | 33x+57=33x+61 | | -5(2n-3)-6=3(5n+1)-8 | | ax-bx=15 | | 7-2x=6x-30 | | 11x-21=5+7x | | -21+-15=x | | -9(8x)= | | 5x/8=6 | | (-5r^4s^2)(9s^3-7r+4)= | | 5(7x-6)-4=35x-34 | | (-5r^4)(s^2)(9s^3-7r+4)= | | 2x^-2/3x | | -31=x-19 | | -7x+11=116 | | (1+100/100*(100/100-0.14)/3.4)=5 | | x-0.2=5 | | 1/2x-2/3x=4x | | 36x+6=27-3x | | (1+100/100*(100/100-0.14)/3.4) | | x-0.2x=5 | | 41x+599x-87=41(40x+61) | | -7x+11=16 | | 3x+x+7=8x-4x+7 | | 36*4/9 | | -4=k-7+1 | | -4a-27=3(7a+1)-5 | | 3(6x+9)+4x=82 | | 3x+19=13x-21 | | (1/x)+(6/(x-4))=0 |